Analysis of traffic safety on the roads of the Kharkiv region during the period of martial law - Riabushenko, Oleksandr; Popadynets, Dmytro; Vorontsov, Yaroslav; Рябушенко, Олександр Васильович; Попадинець, Дмитро Миколайович; Воронцов, Ярослав Сергійович (Харківський національний автомобільно-дорожній університет, 2024)
Problem. The functioning of road transport in regions of long-term armed conflicts is associated with additional risks for road traffic safety. The degree of influence of additional risk factors can be investigated by analyzing traffic accident statistics in such a region. Goal. The purpose of the work is to study the impact of martial law conditions on road safety indicators in the Kharkiv region of Ukraine by comparing statistical data on accidents and road deaths due to road accidents. Methodology. To achieve the goal, the work uses methods of statistical analysis of data and construction of trends, methods of determining relative indicators of the severity of road accidents. Results. As a result of the analysis of statistical data on road accidents in the Kharkiv region, the distribution of accident rates for the period from 2019 to 2023 was obtained, which made it possible to reveal their significant differences during the period of martial law compared to previous periods. In particular, it was established that with a decrease in the total number of road accidents, there was an increase in the severity of the consequences of road accidents. This regularity was confirmed by analyzing the relative indicators of road accident severity. The identified differences in accident and death rates on the roads of the Kharkiv region in 2023 compared to the periods before the start of hostilities indicate a change in road traffic conditions. Originality. The paper investigated the impact of martial law conditions on road safety on the example of the Kharkiv region of Ukraine. As a result, the degree of influence of the risk factors that arose as a result of the deployment of the armed conflict on the increase in the level of danger for road users was established. Practical value. The obtained results can be used for planning and implementation of measures to ensure traffic safety on highways in regions that are the zone of long-term armed conflicts.
Аналіз безпеки руху на дорогах Харківської області в період воєнного стану
Keywords: road traffic; road safety; road traffic accidents; martial law conditions; severity factor; distribution of road accidents; дорожній рух; безпека дорожнього руху; дорожньою-транспортні пригоди; умови військового стану; коефіцієнт тяжкості; розподіл ДТП; 656.1.5; 10.30977/AT.2219-8342.2024.54.0.04